An experimental investigation of the trajectory of single molecule particles in methyl cellulose hydrogel - Tan, Kristine Chye Lay. (2010)
The development of single molecule spectroscopy and imaging techniques removes the usual ensemble average, allowing the exploration of heterogeneity in many complex